Oficina - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Oficina de la Municipalidad Distrital de Fernando Lores, Oficina telefonica rural - Tamshiyacu, El Distrito de Fernando Lores es uno de los 11 distritos de la Provincia de Maynas, ubicado en el Departamento de Loreto, Su capital es la ciudad de Tamshiyacu
ENGLISH: Office of the District Municipality of Fernando Lores, Rural telephone office - Tamshiyacu, The District of Fernando Lores is one of the 11 districts of the Province of Maynas, located in the Department of Loreto, Its capital is the city of Tamshiyacu.

SPANISH: Oficina de la Municipalidad Distrital de Fernando Lores, Oficina telefonica rural - Tamshiyacu, El Distrito de Fernando Lores es uno de los 11 distritos de la Provincia de Maynas, ubicado en el Departamento de Loreto, Su capital es la ciudad de Tamshiyacu
ENGLISH: Office of the District Municipality of Fernando Lores, Rural telephone office - Tamshiyacu, The District of Fernando Lores is one of the 11 districts of the Province of Maynas, located in the Department of Loreto, Its capital is the city of Tamshiyacu.
Office
Keywords: Iquitos (Perú)|~|Office--Municipality|~|Oficina|~|Municipalidad|~|Iquitos (Perú)